Cabo de sombrinha romana de marfim achado em Oeiras (Portugal) - Rodríguez Martín, Germán (2020)
In the archaeological excavations carried out in 2017 in the Historic Center of Oeiras (Lisbon, Portugal), an ivory parasol handle was collected in a Roman context whose chronology does not exceed the end of the 2nd century AD. This is the first time that a specimen of this nature it is identified in the Iberian Peninsula, underlining its extreme rarity, whose use was reserved for the ladies of the social elite of the time.